KONSUMSI AIR REBUSAN JAHE DAPAT MENGURANGI NYERI DISMENOREA PADA SISWI DI SMKN 10 MUARO JAMBI - Simanjuntak, Ry Eny Mian Marisi Br.; Lestari, Ayu; Nurmisih, Nurmisih; Wuryandari, Ajeng Galuh (NHM PRESS, 2024)
Reproductive health in women is currently a health issue that still needs attention, as reproductive health is not just about being free from diseases and disabilities related to the reproductive system, functions, and processes, but also being physically, mentally, and socially healthy as a whole. This study is a quasi-experimental research with a two-group pretest-posttest design to determine the effectiveness of consuming ginger decoction on dysmenorrhea pain in female students at SMKN 10 Muaro Jambi. The study was conducted from January to July 2023. The research population consisted of all 10th and 11th-grade students in the 2022/2023 academic year, totaling 105 individuals. The sample included 30 respondents selected using quota sampling techniques. Data collection was carried out using the Numeric Rating Scale to assess dysmenorrhea pain levels in adolescents. Data were analyzed univariately and bivariately using the Wilcoxon and Mann-Whitney tests. The results of this study indicate that ginger decoction (p-value 0.001) significantly affects dysmenorrhea pain in female students, as the p-value is less than 0.05. Ginger decoction is effective in reducing dysmenorrhea pain in female students. Therefore, it is expected that the school will promote health regarding the use of ginger decoction to address menstrual issues, including dysmenorrhea pain, which can be recommended to reduce and alleviate dysmenorrhea pain.